Factors influencing performance of entrepreneurs of farmers market in Malacca - Wan Bakar, Wan Mohd Marzuki; Mohd Nawi, Nolila; Abdul Rahman, Arifuddin (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
This study aims to find and explore the factors influencing performance of farmer’s market entrepreneurs in Malacca and the association between respondent’s demographic profile and performance. A survey was conducted using structured questionnaire which was distributed among entrepreneurs in farmers market around Malacca in 15 different locations. Respondents were selected using proportionate stratified sampling method and a total of 175 respondents participated in this study. Chi-square analysis and factor analysis were carried out to analyze the data. In this study, the result shows that there are association between respondent’s demographic profile and entrepreneurs’ performance (financial and non-financial) at farmers market around Malacca. Furthermore, four factors were extracted from exploratory factor analysis which is network, environment, entrepreneurial learning and individual motivation. All the four factors are significant in influencing the performance of farmer’s market entrepreneurs. In order to increase the performance of farmer’s market entrepreneurs, entrepreneurs themselves should be more creative in doing their sales activity. FAMA and related agencies should also provide farmers market entrepreneurs with more courses and training related to entrepreneurship development.